WATAK KATO DALAM BAHASA MINANGKABAU: Sebagai Cerminan Perilaku Berbahasa Masyarkat Minangbakabau - Leni Syafyahya; Efriyades Efriyades; Delfia Elly (Masyarakat Linguistik Indonesia Universitas Andalas, 2015)
The inappropriate use of nick name in dialy life may lead to misunderstanding in the interaction. It is because nickname has kato character or'word of manners' in its particular use. The paper will explain the forms nickname, Kato character contained in the nickname, lexical variation and variation of use of nickname. The paper is derived from the results of our research. Technically, the data are collected by using observational method and conversational method. Proficient method can be aligned with the interview method. The analysis of the data are conducted by using editing (examining the completeness and reliability of the data) and coding (classification data). Then the process is continued by interpreting the validity of the data that has been coded along with the appropriate theories. Moreover, the data analysis is conducted by using identity method and distributional method. Based on data analysis it can be foun found the form of nickname, Kato character contained in the nickname, lexical variation and variation of use. Nickname in Minangkabau language may take either complete form or incomplete form. From both complete and incomplete forms, kato characters can be categorized into 4 types, ie.'Kato mancari kawan' (friendship nickname), 'Kato mancari lawan (insulting nickname)' Kato indak bakawan' (unfriendly nickname), and 'Kato indak Balawan' non-opponent nickname. Moreover, the nickname in Minangkabau language has lexical variation and variation of use. Lexical variation occurs because of differences in the area of ​​use, while the variation of use occurs because of certain intention. Lexical variation can also occur in the in one particular area or in same area as well as the variation of its use.